2020
DOI: 10.1093/gerona/glaa113
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance Between Omega-6- and Omega-3-Derived Bioactive Lipids in Arthritis in Older Adults

Abstract: Elderly-onset rheumatoid arthritis (EORA) and polymyalgia rheumatica (PMR) are common rheumatic diseases in older adults. Oxylipins are bioactive lipids derived from omega-6 (n-6) and omega-3 (n-3) polyunsaturated fatty acids (PUFAs) that serve as activators or suppressors of systemic inflammation. We hypothesized that arthritis symptoms in older adults were related to oxylipin-related perturbations. Arthritis in older adults (ARTIEL) is an observational prospective cohort with 64 patients older than 60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The n-3-related oxylipins generally are anti-inflammatory, anti-proliferative and proresolving [10]. Imbalances in n-6 and n-3 oxylipins have been found in patients with the autoimmune conditions ulcerative colitis [11] and arthritis [8,12,13]. In healthy DAISY participants without type 1 diabetes, we found that most oxylipins were significantly associated with their precursor FA (e.g.…”
Section: Introductionmentioning
confidence: 62%
“…The n-3-related oxylipins generally are anti-inflammatory, anti-proliferative and proresolving [10]. Imbalances in n-6 and n-3 oxylipins have been found in patients with the autoimmune conditions ulcerative colitis [11] and arthritis [8,12,13]. In healthy DAISY participants without type 1 diabetes, we found that most oxylipins were significantly associated with their precursor FA (e.g.…”
Section: Introductionmentioning
confidence: 62%
“…DHETs are the metabolites of EETs hydrolyzed by soluble epoxide hydrolase (sEH) (Yang et al, 2013 ). PGB2 is the metabolite of PGE2 (Coras et al, 2021 ), and PGE2 can promote cell growth and elevate the expression of hypertrophic marker genes by inhibiting the COX2/PGE2 pathway (Zhang et al, 2019 ). PGJ2 is formed by dehydration within the cyclopentenone ring of PGD2 (Abdelrahman et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the significantly increased TSH level with increased PGB2 and the significantly decreased VD3 level with increased PGB2 and PGJ2 were detected in high iodide intake–induced hypothyroidism. PGB2 is the metabolite of PGE2 (Coras et al, 2021 ), and PGJ2 is formed by dehydration within the cyclopentenone ring of PGD2 (Abdelrahman et al, 2004 ). Tahara et al ( 1991 ) reported that TSH stimulates the production of PGD2 and PGE2 in the Fischer rat thyroid follicular cell line (FRTL-5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitely, it is necessary to keep in mind that prevention is the best treatment. In this sense, a healthy diet based on incorporation of a wide variety of nutrients and preventive nutrition could contribute to reduce the appearance of diseases that arise as a consequence of a deficient or improper diet as several studies suggest could happen with RA [ 33 , 249 , 269 , 303 ]. This way requires the participation of different sectors, both public and private, with national policies that promote a healthy diet.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%